Populations and host/non-host plants of Spittlebugs Nymphs in olive orchards from Northeastern Portugal - Villa, Maria (2020)
The Aphrophoridae family contains important vectors of Xylella fastidiosa, a serious bacterial plant disease. In olive orchards, nymphs usually feed on the ground-cover vegetation. However, detailed information about their populations and host/non-host plants in some regions threatened by Xylella, such as the northeast of Portugal, is very limited. The goal of our work was to identify the vector species, nymphal development period, and their host and non-host herbaceous plants in olive orchards from northeastern Portugal. Ground-cover plant species hosting or not hosting nymphs were identified during the spring of 2017 to 2019 in olive orchards. Nymphal development period, nymph aggregation, and nymph's preferred feeding height of the ground-cover plants were recorded. The most abundant Aphrophoridae species was Philaenus spumarius followed by Neophilaenus sp. Nymphs developed from April to early May and showed a low number of individuals per foam (generally between one and three). They preferred the middle part of the plants. Philaenus spumarius feeds preferentially on Asteraceae and Fabaceae, and Neophilaenus sp. on Poaceae. Some abundant plants, such as Bromus diandrus, Astragalus pelecinus, Chrysanthemum segetum, Trifolium spp., Caryophyllaceae, and Brassicaceae, were barely colonized by Aphrophoridae nymphs. This knowledge is essential for the selection of the species composition of ground-cover vegetation to minimize the presence of vectors of X. fastidiosa in olive groves.